1991
DOI: 10.1007/bf00909975
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic memory in learning-disabled and skilled readers

Abstract: Three experiments compared learning-disabled and skilled readers' performance on naturalistic memory measures, as well as investigated the relationship between memory performance on everyday and laboratory tasks. In Experiment 1, the laboratory task (sentence span task) and everyday memory measures were correlated moderately for both ability groups. Compared to skilled readers, disabled readers performed poorly on the sentence span task, and were less likely than skilled readers to remember information related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Our studies therefore raise some interesting questions about the potential for strategy instruction to improve recall. Several studies have investigated the effect of implicit cues to recall and have found that, when provided with cues, students with dyslexia can increase recall performance levels to those of non-dyslexics (e.g., Swanson et al, 1991;Torgesen & Goldman, 1977;Wong, 1978). Much of this research presented verbal information, an exception being Swanson (1984) who found that students with dyslexia performed better than a control group when cued to retrieve complex visual information that could not be encoded verbally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies therefore raise some interesting questions about the potential for strategy instruction to improve recall. Several studies have investigated the effect of implicit cues to recall and have found that, when provided with cues, students with dyslexia can increase recall performance levels to those of non-dyslexics (e.g., Swanson et al, 1991;Torgesen & Goldman, 1977;Wong, 1978). Much of this research presented verbal information, an exception being Swanson (1984) who found that students with dyslexia performed better than a control group when cued to retrieve complex visual information that could not be encoded verbally.…”
Section: Discussionmentioning
confidence: 99%
“…People with dyslexia are known to experience difficulties with memory during many ordinary everyday activities, such as recalling a range of naturalistic objects (Swanson, et al 1991) remembering details of everyday events, social situations, and procedures such as checking out a book from the library (McNamara and Wong, 2003). These results are often explained in terms of an executive deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Recall of coins and other familiar objects has been used previously to measure 'everyday memory' (e.g. McNamara & Wong, 2003;Swanson, Reffel, & Trahan, 1991). However, in these studies participants were required to draw the items in as much detail as possible.…”
Section: Measures Of Visuospatial Ability and Recallmentioning
confidence: 99%
“…Indeed, narrative reports have provided much valuable data in the study of naturalistic memory (e.g., G. Cohen, Conway, & Maylor, 1994;Marian & Neisser, 2000). However, tests that elicit and record nonverbal, perceptual content or productions from memory appear very rarely in research on memory for naturally occurring events (e.g., Martin & Jones, 1998;Rubin & Kontis, 1983;Swanson, Reffel, & Trahan, 1991), and in basic experimental studies of memory (e.g., Amrhein & Sanchez, 1997;Santa & Baker, 1975). Yet many events, especially television commercials and other complex everyday occurrences, have numerous nonverbal, visual features that eliciting verbal responses alone may not assess completely.…”
Section: Nonverbal Memory In Basic and Applied Researchmentioning
confidence: 98%